Comparison studies between pressure-controlled pump with conventional pump for domestic application - Siti Aisyah, Jilani (2024)
The source and infrastructure that distributes water to residences are referred to as the domestic water supply. Pumping is an important way for obtaining water from various resources where gravity alone is insufficient due to geography and side levels. Centrifugal pumps are the most common type of pumps used in residential applications. This kind of pump is affordable and simple in design. Domestic centrifugal water pumps motor conventionally works at constant speed and provide a constant output. However, constant speed pumps are not easily able to deal with changing demands in water flows which will yield excessive energy losses and water losses. Various methods of energy saving in pumping applications have been applied by several groups of researchers, such as bypass lines, throttle control, parallel pumps, and variable speed control. Therefore, this research was commenced to study pressure-controlled variable speed pumps. This research aimed to study and compare the performance of constant speed and variable speed pumps in terms of performance characteristics like water pressure, flow rate, and pump speed. Moreover, this research also aimed to analyze energy cost saving offered by the variable speed water pump. In this research, a suitable technique was proposed to change the constant speed pump to a variable speed pump by adding Variable Frequency Drive (VFD) to the conventional pump’s motor to control the speed of the pump to match the water load demand. A simple and inexpensive test rig was designed and fabricated to represent water distribution for domestic use for example single-storey home application. The method is then experimentally validated to verify the pump performance and energy saving between conventional and variable speed water pumps. The valve opening which is half open and full open also was tested to see the variation of volume flowrate and pressure difference. For the pressure-controlled variable speed pump, to maintain the pressure inside the pipe to 20.68 kPa, the speed was controlled by adjusting the frequency. The results demonstrated that variable-speed pumps are the best option for matching the required loads, saving energy and water while also increasing the economic features of electrical motors. So, we conclude that less energy is applied when the motor runs at lower speeds. Pump energy, pressure, and volume flow rate are all influenced by the valve opening. A lower volume flow rate is achieved with a smaller valve opening, which reduces energy consumption where inversely correlated to pipe pressure. Pump pressure will rise by the time the valve opening is decreasing. The smallest opening of the valve for a pressure-controlled variable speed pump can reduce energy consumption by about 92% in comparison to a conventional water pump.